Effect of mechanical seed scarification on germination and seedling growth of inter specific hybrids of oil palm (Elaeis oleifera) - MURUGESAN, P; RAVICHANDRAN, G; SHAREEF, M (The Indian Journal of Agricultural Sciences, 2015)
The mechanical scarification techniques were tried to break the seed dormancy of wild oil palm (Elaeis oleifera HBK) with an objective to get speedy, uniform germination and seedlings to facilitate precise evaluation of progenies of inter specific hybrids. The experiment was conducted using hybridized and freshly processed Elaeis oleifera seeds from Palm No. 6 planted during 1994. A total of six mechanical scarification techniques along with dry heat treatment were adopted to achieve the objective. The results revealed that chipping endocarp (removing round piece of endocarp containing germ pore) of the nut and de-operculum (removing plate like structure present in the seed coat above the embryo in the kernel) resulted in maximum germination with uniform seedlings production. Endocarp chipping combined with de-operculum resulted in maximum germination with 50% and took 3, 5 and 7 days to initiate germination, 50% germination and final germination (50%), respectively. Dry heated seeds took 15 days time to attain maximum germination (40%) after pre heating duration of 60 days in the heating room. One set of seeds which received hammer crack in nut germpore region remained dormant even after six weeks due to ineffective scarification. Hence, nut chipping and de-operculum technique is recommended to alleviate the dormancy and the successful treatment could be adopted for production of quality planting material in inter specific hybrid seeds.